The initial stage of high-pressure induced β-lactoglobulin aggregation: The long-run simulation - Baars, Albert; Delgado, Antonio; Reznikov, Gennadiy (International Journal of Food Science and Technology, 2011)
Research objective of this study was to clarify how the initial stage of high-pressure induced aggregation of β-lactoglobulin takes place. For this purpose a special simulation method was developed. Distinctive features of this approach are: the lowest resolution model of protein particles, the local interaction potential and the abandonment of the continuous simulation of particle trajectories. Relatively short molecular dynamics trajectories are used only in order to find the average time step between the collisions. Results of particle collisions that occur with some probability, are separately ('statically') modelled using a random variable. This allows the analysis of the process which takes place within 10 2-10 3s real-time, with an existing probability of successful collision of 10 -10-10 -11. Modelling results confirm that at the initial stage of aggregation of 0.5-2% solutions with a neutral pH-value only dimers as well as trimers arise due to SH/S-S interaction. In addition it was shown that aggregation follows the general principles of the reaction-limited aggregation of colloids. The proposed approach could further be used in research projects examining the aggregation of β-lactoglobulin or similar systems. © 2011 The Authors. International Journal of Food Science and Technology © 2011 Institute of Food Science and Technology.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.theini
Keywords: β-lactoglobulin; Aggregation; High pressure; Molecular dynamics; Random variable